EFEKTIFITAS PENGGUNAAN MODEL PEMBELAJARAN PBL BERBANTUAN MACROMEDIA FLASH 8 TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS X DI SMK NEGERI 1 BATANGTORU - Jerni Mattauli Sitohang (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2018)
This study aims to describe the effectiveness of using PBL learning model by helping macromedia flash 8 on students’ critical thinking ability at the tenth grade students of SMK negeri 1 Batangtoru. This research was conducted by applying experimental method (pretest post test one group design) with 30 students as the sample and they were taken by using random sampling from 122 students. Observation and test were used in collecting the data. Based on the data analysis, it was found that: (a) the average of using PBL learning model by helping macromedia flash 8 was 3.9 (very good category) and (b) the average of students’ critical thinking ability before using PBL learning model by helping macromedia flash 8 18.23(poor category) and after using PBL learning model by helping macromedia flash 8 was 85.07(good category). Furthermore, based on inferential statistic by using paired sample ttest and helping SPSS 16, the result showed the significant value was less than 0.05 (0.000 < 0.05). It means, PBL learning model by helping macromedia flash 8 was effective used on students’ critical thinking ability at the tenth grade students of SMK Negeri 1 Batangtoru.